2017
DOI: 10.3389/fnana.2017.00045
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin Fragments Deposit at Senile Plaques in Human Cerebrum

Abstract: Genetic variations in the vacuolar protein sorting 10 protein (Vps10p) family have been linked to Alzheimer’s disease (AD). Here we demonstrate deposition of fragments from the Vps10p member sortilin at senile plaques (SPs) in aged and AD human cerebrum. Sortilin changes were characterized in postmortem brains with antibodies against the extracellular and intracellular C-terminal domains. The two antibodies exhibited identical labeling in normal human cerebrum, occurring in the somata and dendrites of cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 93 publications
6
45
0
Order By: Relevance
“…Further understanding of the neurobiological and neuropathological roles played by this family of proteins might extend novel AD diagnostic and therapeutic options. We recently reported that putative C-terminal fragments from sortilin can deposit in aged and AD human brains as extracellular lesions morphologically appearing as senile plaques [ 61 ]. The deposition occurs fairly selectively at neuritic amyloid plaques, as visualized with an antibody (catalog number ab16640; Abcam, Cambridge, UK) targeting the intracellular C-terminal domain of sortilin, which is evolutionarily conserved among mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Further understanding of the neurobiological and neuropathological roles played by this family of proteins might extend novel AD diagnostic and therapeutic options. We recently reported that putative C-terminal fragments from sortilin can deposit in aged and AD human brains as extracellular lesions morphologically appearing as senile plaques [ 61 ]. The deposition occurs fairly selectively at neuritic amyloid plaques, as visualized with an antibody (catalog number ab16640; Abcam, Cambridge, UK) targeting the intracellular C-terminal domain of sortilin, which is evolutionarily conserved among mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al from Tiantan Hospital of Capital Medical University demonstrate that diffuse intrinsic pontine glioma exhibits the cell-biological and molecular signatures of fetal hindbrain-derived neural progenitor cells [30]. The research reports included in the current special issue, together with others recently published elsewhere [31][32][33][34][35], clearly showcase that brain banking in China can support important original investigations for the better understanding of human brain structure and function. It can be expected that, with further progress on this front, additional discoveries will emerge and help unravel the underpinnings of major neurological, psychiatric, and developmental brain diseases affecting the Chinese people.…”
mentioning
confidence: 67%
“…Brain samples were cut into 30 µm thick coronal sections and collected in serial sets as previously described using a cryostat (Leica CM3050S, Buffalo Grove, IL, United States). Consecutive sections from each animal were stained with cresyl violet (Nissl stain), hematoxylin/eosin (HE) and primary antibodies with the avidin-biotin complex (ABC) method or fluorescent-tagged secondary antibodies as previously described (Hu et al, 2017). The primary antibodies used including the following: NLRP3 (1:200, Cat#ab4207, Abcam, United States), ASC (1:200, Cat#sc-51414, Abcam, United States), 8-OHdG (1:200, Cat#ab48508, Abcam, United States), DCX (1:200, Cat#ab18723, Abcam, United States), and fibrinogen (1:500, Cat# LS-B11024, Lifespan, United States).…”
Section: Histological Immunohistochemical and Immunofluorescent Stainsmentioning
confidence: 99%